(3TQa GdWGdH aj CSfi GdeWGdHs - (3GHf bfaP , CHh GdYHGS CMeO Hf GdMSjf Hf Ydj Hf GdNWjH Hf bfaP GdbSfWjfj, GHf GdNWjH, GHf bfaP,J (B810 (3g` s
(3ChdgG (B:s
(3GPcQ ai gPG GdJCdja eG MVQfi ef haGI GdUMGHI hGdYdeGA hGdeMOKjf hGdeDdajf , hQJHJg Ydi GdeFjf , HhLg de CSHb Edjg s
(3BNQgG (B:s
(3hbO CPfJ def QBfi Ch QCi ef QBfi ,hgeG OQLJGf , Cf jMOK Yfi EP TGA eG TGA ef eUfaGJi , Ch eG UM dOjg ef eQhjGJi s
(3HBNQ GdcJGH fHPI Yf GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B117 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B205s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B241 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B341 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B255 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(102 (3O(B) s
Keywords: (3GdJGQjNs